2013
DOI: 10.1142/s1793604712500518
|View full text |Cite
|
Sign up to set email alerts
|

Metal-to-Dielectric Transition Induced by Annealing of Oriented Titanium Thin Films

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible.This is an author-deposited version published in: http://sam.ensam.eu Handle ID: .http://hdl.handle.net/10985/7486 To cite this version :Aurélien BESNARD, Nicolas MARTIN, Nicolas STAHL, Luc CARPENTIER, Jean-Yves RAUCHMetal-to-Dielectric transition induced by annealing of oriented titanium thin films -Functional Materials Letter -Vol. 6, n°1, p.5 -2013 Any cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
3
8
0
Order By: Relevance
“…Consequently, more intercolumnar voids are created, thus the porosity of the GLAD deposited films is increased. This porosity increase is also closely related with the increase of the number of zigzag periods [22,26,29,39,42,60]. The obtained ß angles corroborate the morphology and porosity changes, since they vary from a minimum of 23°(for the compact α = 40°sample) to an average of 29°for the porous films.…”
Section: Rbs Composition Analysis (Performed In Different Points Of Tsupporting
confidence: 77%
See 1 more Smart Citation
“…Consequently, more intercolumnar voids are created, thus the porosity of the GLAD deposited films is increased. This porosity increase is also closely related with the increase of the number of zigzag periods [22,26,29,39,42,60]. The obtained ß angles corroborate the morphology and porosity changes, since they vary from a minimum of 23°(for the compact α = 40°sample) to an average of 29°for the porous films.…”
Section: Rbs Composition Analysis (Performed In Different Points Of Tsupporting
confidence: 77%
“…Thus, GLAD thin films, prepared by either evaporation or magnetron sputtering are becoming an attractive strategy to obtain a wide variety of architectures and sculptured materials at the micro-and nanoscale. This involvement is mostly evident for metal and oxide coatings sputter deposited with inclined architectures [39][40][41][42][43] but very few studies are dedicated to metallic nitrides produced by the GLAD technique [44][45][46], especially regarding the relations between the possible achieved structures by GLAD (e.g. inclined columns, zigzags, spirals) and the resulting properties in terms of mechanical response, electrical conductivity or even electrochemical behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Film growth with an oblique incidence is a well-known phenomenon. The microstructure and the morphology can strongly be modified according to the incidence angle value, leading to the presence of porosity [47]. As previously observed by Charles et al, the diminution of the transmittance with the incidence angle could be also ascribed to a change in the porosity of the microstructure [48].…”
Section: Optical Properties Of the Feox Filmsmentioning
confidence: 85%
“…In addition, it was previously shown that GLAD films become strongly porous for α4601 (due to extreme shadowing). Oxidation of the film is also enhanced when heated at 250 1C [19]. Thus oxygen deficiencies are strongly reduced and cannot be considered as the main criterion influencing the sensor performances.…”
Section: Resultsmentioning
confidence: 99%